# math 116

posted by .

6-2(3x-3) =-18
6-6x-6=-18
12x=-6=18=24
12x=24
x=2
check this problem is it right.

• math 116 -

no
6-2(3x-3) =-18
6-6x+6=-18
-6 x + 12 = -18
-6 x = - 30
x = 5

check
6 - 2(15-3) = -18???
6 - 24 = -18
-18 = -18 yes, check

• math 116 -

6-2(3x-3) =-18
6-6x-6=-18
12x=-6=18=24
12x=24
x=2

Your first step is incorrect. When you multiply two negatives, the answer is a positive.
6 - 6x + 6 = -18

I don't know where you got 12x.

6-2(3x-3) =-18
6 - 6x + 6 = -18
12 + 18 = 6x
5 = x

Check it out by substituting 5 for x in your original problem.

## Similar Questions

1. ### calc

What is dy/dx of y=12/12X-y^3 ???? Any idea anyone?
2. ### algebra2

1/3 - 5/6 = 1/X SOLVE 1/3 - 5/6 = 1/X Let's remove the denominators by multiplying by 12X 12X*(1/3) - 12X*(5/6) = 12X*(1/X) Clear the fractions. 4X - 10X = 12 -6X=12 multipy by -1 6X=-12 Divide both sides by 6 6X/6 = -12/6 X = -2 Check …
3. ### algebra1

could you walk-through the steps to solving this problem because I am stuck; 3x-5(3x-7)=2(x+9)+45 Let me know if you have a question in any step. 3x-5(3x-7)=2(x+9)+45 3x-15x+35= 2x+18+45 -12x+35 = 2x+63 -35 -35 -12x= 2x +63-35 -12x= …
4. ### algebra

Can anyone tell me if I got this problem right 12x-6=11x 12x-6+6=11x+6 12x-11x=6 1x=6 x=6/1 x=6 Yes, that is correct
5. ### Polynomial Fucntion Problem

Could you help me with the following problem, I don't understand how to do it. Am I suppose to use the linear factorization theorem?
6. ### Algebra

Can someone please check my work for me. Q: Plot the graph of the equations 2x - 3y = 5 and 4x - 6y = 21 and interpret the result. A: 6(2x ¨C 3y = 5) = 12x ¨C 18y = 30 3(4x - 6y = 21) = 12x - 18y = 63 12x ¨C 18y = 30 + 12x - 18y …
7. ### algebra

(12x+1)(x-1)=-3 12x^+1=-3 12x^=-1-3 x=1/3 check this problem
8. ### algebra

24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3-12x check this problem for me please
9. ### math

solve algebraically and check y=8x+3 y=-4x-21 8x+3=-4x-21 +4x +4x 12x+3=-21 -3 -3 12x=-24 x=-2 y=8x+3 y=8(-2)+3 y=-16+3 y=-13 (-2,-13) check y=8x+3 -13=8(-2)+3 -13=-16+3 -13=-13 y=-4x-21 -13=-4(-2)-21 -13=8-21 so -13=-13 these check, …